2020
DOI: 10.1101/2020.03.24.004796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Full-length genome sequence of segmented RNA virus from ticks was obtained using small RNA sequencing data

Abstract: In 2014, A novel tick-borne virus of the genus Flavivirus was first reported from the Mogiana region in Brazil. This virus was named the Mogiana tick virus (MGTV). Later, MGTV was also named as Jingmen tick virus (JMTV), Kindia tick virus (KDTV), Guangxi tick virus (GXTV) etc. In the present study, we used small RNA sequencing (sRNA-seq) to detect viruses in ticks and detected MGTV in Amblyomma testudinarium ticks, which had been captured in Yunnan province of China in the year of 2016. The fulllength genome s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The recovery of complete segmented viral genomes from metagenomics or viromics datasets is particularly challenging due to their segmented nature. Previous studies have used co-occurrence of viral contigs in other publicly available datasets [ 50 ] or sequence homology to known viral species [ 51 ], however the lack of suitable publicly available datasets and extensive horizontal gene transfer can hamper these efforts. Unlike other members of the Botourmiaviridae family, viruses of the genus Ourmiavirus are known to possess coat proteins that show similarity with highly disparate viruses spanning multiple phyla [ 16 ] and with only three classified species of this genus known, reconstructing their full genomes and classifying novel ourmia-like viruses is particularly challenging.…”
Section: Resultsmentioning
confidence: 99%
“…The recovery of complete segmented viral genomes from metagenomics or viromics datasets is particularly challenging due to their segmented nature. Previous studies have used co-occurrence of viral contigs in other publicly available datasets [ 50 ] or sequence homology to known viral species [ 51 ], however the lack of suitable publicly available datasets and extensive horizontal gene transfer can hamper these efforts. Unlike other members of the Botourmiaviridae family, viruses of the genus Ourmiavirus are known to possess coat proteins that show similarity with highly disparate viruses spanning multiple phyla [ 16 ] and with only three classified species of this genus known, reconstructing their full genomes and classifying novel ourmia-like viruses is particularly challenging.…”
Section: Resultsmentioning
confidence: 99%
“…As its initial identification in the Jingmen region of Hubei province in 2010 and description in 2014, JMTV has been confirmed in several other regions in China, such as Zhejiang, Guizhou, Yunnan, Guangxi, Henan, Xinjiang, and Heilongjiang province (Guo et al, 2020;Jia et al, 2019;Meng et al, 2019;Shi et al, 2021;Xu et al, 2020;Yu et al, 2020). Subsequently, JMTV was reported around the world, including Kenya, the UK, the USA in 2015, Uganda in 2016, Kosovo and Brazil in 2018, Trinidad and Tobago, Turkey, Laos, and French Antilles in 2019 (Dincer et al, 2019;Temmam et al, 2019;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…The first group comprised JMTV from Asia, Africa, Eastern F I G U R E 2 Summary of study design Since its initial identification in Jingmen region in 2010, JMTV has been confirmed in many regions both inside and outside of China. 9,10,16 More importantly, it has been reported that JMTV was associated with human febrile diseases in China and Kosovo, and this virus could be a causative agent of human disease. 12,13 Therefore,…”
Section: Phylogenetic Analysismentioning
confidence: 99%